Impact of Audiovisual Content Consumption on the Self-Esteem of University Students - Garro-Aburto, Luzmila Lourdes; Vicuña Salvador, Hermilio Hugo; Carrillo-Flores, Jorge Wilfredo; Sánchez Sánchez, Rosa Marlenne (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Audiovisual content, including movies, series, and social networking videos, play a crucial role in the personal and social development of college students, underscoring the importance of understanding their impact on student well-being. This study aimed to identify trends that contribute to the development of educational strategies and guidelines that improve the psychological health of the student community. A sample of 601 students, aged 16 to 27 years, was analyzed using self-esteem and audiovisual media consumption questionnaires. The results reveal that moderate and selective consumption of content, especially movies, is associated with higher self-esteem. On the contrary, excessive consumption and preference for certain contents, such as series, are associated with lower self-esteem. These results underscore the importance of conscious media consumption, urging students to select content that promotes their emotional health.